Pengembangan Aplikasi Komunitas Rukun Warga berbasis Mobile - Ibrahim Hafizhuddin Muttaqi; Herman Tolle; Buce Trias Hanggara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The rapid development of Information Technology (IT) facilitates various fields, including the government sector. The application of IT in the government sector is carried out in the application of the smart city concept which consists of the application of 6 pillars. The application of the smart city concept in Malang City has been echoed since 2014 and is targeted for completion in 2022. Of the six pillars of smart city, smart governance is the pillar related to bureaucratic affairs. RW 12 Tulusrejo Village is one of the areas that requires the implementation of smart governance. RW 12 has 3 services, namely information services, finance, and letter submission. However, the implementation of these services is not optimal due to several obstacles. The first obstacle is that the data stored is still in the form of printed archives, making it difficult to provide data. The second obstacle is the pandemic situation in Indonesia which makes residents a bit afraid to meet in submitting letters. The third obstacle is the busyness of the RT and RW management which makes them not in place so that it hinders residents who want to submit letters. Therefore, a mobile application for the Rukun Warga community service was developed using the MASAM development method and the flutter framework. The results of the application design produce 16 use cases and the results of testing applications that are built on the usability side produce an SUS value of 70 for citizen applications and an SUS value of 68.5 for administrator applications.